Temporal database application in industrial human resource management - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2014)
Temporal database is an established database technology which has recently been introduced to the industrial and commercial world. Temporal database features are available through specialized modules of commercial database management systems (DBMS). The SQL 2011 standard also includes temporal database features; even though at the time of this paper writing, not many DBMS products comply with the standard. We found temporal database features suitable for human resource applications and apply it in a rubber processing plant in southern Thailand. This paper demonstrates the temporal database design using a conceptual schema approach and temporal database implementations at the SQL level.
Keywords: Hr management; Oracle workspace manager; Orm/niam; Temporal database